2007
DOI: 10.1080/09638280600756208
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for successful vocational rehabilitation for clients with back pain problems

Abstract: The findings regarding age, general health and vitality are well in line with previous studies. The findings regarding internal locus of control are more unique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 18 publications
1
18
1
5
Order By: Relevance
“…This is consistent with previous research, which showed that individuals' perceived control influences the outcome from vocational rehabilitation (Millet, 2005;Selander et al, 2007). Furthermore, the present study showed that responders and nonresponders to an MVRP differed significantly at baseline in terms of the sense of mastery and pain intensity variables, where the outcome in terms of WA was affected by the sense of mastery and the pain intensity at baseline.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with previous research, which showed that individuals' perceived control influences the outcome from vocational rehabilitation (Millet, 2005;Selander et al, 2007). Furthermore, the present study showed that responders and nonresponders to an MVRP differed significantly at baseline in terms of the sense of mastery and pain intensity variables, where the outcome in terms of WA was affected by the sense of mastery and the pain intensity at baseline.…”
Section: Discussionsupporting
confidence: 82%
“…The cognitive impairment associated with pain appears to be a major obstacle to rehabilitation (Moriarty, McGuire, & Finn, 2011). Furthermore, individual differences in perceived control are related to a variety of positive outcomes, including vocational rehabilitation, health, achievement, motivation, self-esteem, and coping (Millet, 2005;Selander, Marnetoft, & Åsell, 2007;Skinner, 1996). Generally, conceptualized perceived control or sense of mastery refers to an individual's generalized expectancies or beliefs about the extent to which they regard their life chances and things that happen to them as being under their own control in contrast to being fatalistically ruled (Pearlin & Schooler, 1978;Rotter, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…There were 14 quantitative studies which addressed the possible positive association between feelings of control and work participation (Table 1: Boot et al 2008; Busch et al 2007; Ekberg et al 2015; Karoly et al 2013; Krause et al 2013; Murphy et al 2011; Richard et al 2011; Roesler et al 2013; Selander et al 2007; Sluiter and Frings-Dresen 2008; Torres et al 2009; Truchon et al 2010; Vlasveld et al 2013; Volker et al 2015). The results of six studies indicated that the feeling of having more control is associated with more work participation (Busch et al 2007; Roesler et al 2013; Selander et al 2007; Sluiter and Frings-Dresen 2008; Truchon et al 2010; Vlasveld et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The results of six studies indicated that the feeling of having more control is associated with more work participation (Busch et al 2007; Roesler et al 2013; Selander et al 2007; Sluiter and Frings-Dresen 2008; Truchon et al 2010; Vlasveld et al 2013). These results were supported by one qualitative study by Dionne et al (2013), in which it was reported that participants who did not RTW considered that their return depended more on factors related to their environment than on personal factors.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 LOC-I is associated with greater coping abilities 21 and to the use of more active 22 and adaptive 23,24 coping strategies. In contrast, LOC-C and LOC-P are associated to greater severity of pain and to pain interference in everyday life, [25][26][27] including reduced physical activity 28 and medication abuse.…”
Section: Introductionmentioning
confidence: 99%